2020
DOI: 10.3390/ma13102356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Wetted Zeolite Sands on the Autogenous Shrinkage and Strength of Ultra-High-Performance Concrete

Abstract: In this study, the carrier effect of zeolite sands in reducing the autogenous shrinkage and optimizing the microstructure of ultra-high-performance concrete (UHPC) is studied. Pre-wetted calcined zeolite sand (CZ), calcined at 500 °C for 30 min, and natural zeolite sand (NZ), with 15 wt.% and 30 wt.% in UHPC, are used to partially replace standard sands. On that basis, a series of experiments are executed on the developed UHPC, including compressive strength, autogenous shrinkage, X-ray diffraction (XRD), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…For example, Wang et al [22] studied zeolites calcined at 500 • C for 30 min for use as internal curing agents and found that the efficiency of said calcined zeolites in reducing autogenous shrinkage was significantly improved, and 30% of calcined zeolites reduced the shrinkage by 36% at 28 days. Similar findings were reported in the study by Zhang et al [23], who found that calcination improved the internal pore structure of zeolite sand, enabling it to retain more water, thereby reducing the autogenous shrinkage of ultra-high-performance concrete. However, it should be noted that after calcination at 500 • C, the absorption ability of zeolite sand increased, hence the spalling resistance of concrete containing calcined zeolite sand decreases at elevated temperatures [24][25][26].…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, Wang et al [22] studied zeolites calcined at 500 • C for 30 min for use as internal curing agents and found that the efficiency of said calcined zeolites in reducing autogenous shrinkage was significantly improved, and 30% of calcined zeolites reduced the shrinkage by 36% at 28 days. Similar findings were reported in the study by Zhang et al [23], who found that calcination improved the internal pore structure of zeolite sand, enabling it to retain more water, thereby reducing the autogenous shrinkage of ultra-high-performance concrete. However, it should be noted that after calcination at 500 • C, the absorption ability of zeolite sand increased, hence the spalling resistance of concrete containing calcined zeolite sand decreases at elevated temperatures [24][25][26].…”
Section: Introductionsupporting
confidence: 90%
“…With the AAS system, it is difficult to find the theoretical needed "internal curing liquid." In this study, zeolite sand's replacement ratios (15% and 30%) were taken from reference [23]. In future studies, we will test the chemical shrinkage of AAS according to ASTM C1608 [28], and the results may be used in mixture design to quantify the LWA replacement ratio.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of autogenous shrinkage were selected from NU database [52] (187 observations) and published studies about autogenous shrinkage of low water-to-cement ratio cement paste, mortar or concrete samples incorporating SCM [5,8,10,11,[13][14][15]17,20,21,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][68][69][70][71][72][73][74] and / or SAP [28,29,33,39,[75][76][77][78][79][80][81][82][83][84][85][86]…”
Section: Database Description and Analysismentioning
confidence: 99%
“…Lv et al [5] used natural zeolite in cement systems and determined that the incorporation of 20% natural zeolite reduced the autogenous shrinkage. The addition of zeolite reduced the autogenous shrinkage of high-performance or ultra-high-performance cement-based concrete [4,6,7]. The experiments were based on the substitution of cement with zeolite (up to 15%) or on the replacement of standard sands with zeolite sands (15% and 30%).…”
Section: Introductionmentioning
confidence: 99%